Furfural Production Through Two Bioconversion Routes: Experimental Optimization and Process Simulation - Almeida, S. G. C. [UNESP]; Mello, G. F. [UNESP]; Kovacs, T. K. [UNESP]; Silva, D. D. V. [UNESP]; Costa, M. A.M. [UNESP]; Dussán, K. J. [UNESP] (Springer Nature, 2022)
Purpose: Furfural is a furanic aldehyde obtained from the acid treatment of pentoses found in lignocellulosic material. It has excellent physical and chemical properties that allow its application in the generation of fertilizers, antacids, plastics, paints, fungicides, among many others, besides having important derivatives for the chemical industry, such as furfuryl alcohol and tetrahydrofuran. The production potential of this compound in Brazil is enormous as the country is the world’s largest producer of sugarcane, and the surplus bagasse of this activity is a source of lignocellulosic biomass. Methods: This work experimentally optimized two routes for furfural production: (1) from sugarcane biomass and (2) from the hemicellulosic hydrolysate. Additionally, techno-economic analyses of the optimal sceneries were developed. Results: For the simulation, an initial flow of 71 tonne h−1 of sugarcane biomass was used: case 1 produced 3.93 tonne h−1 of furfural with a heating demand of 44.7 MJ kg−1 (688.7 kW tonne−1 of feed); case 2 produced 2.96 tonne h−1 of furfural with a heating demand of 106.3 MJ kg−1 (1230.3 kW tonne−1 of feed). An economic evaluation of two cases resulted in revenues of U$ 50 million and U$ 31 million for cases 1 and 2, respectively. Furthermore, the internal rate of return (IRR, %) for both cases (72 and 56%, respectively) was greater than the rate of return (ROR = 15%), indicating that the investment will earn profits. Conclusion: Likewise, the integration of furfural production to the first and second-generation (1G and 2G) ethanol production chain could sustain the process, favoring the full use of biomass generating higher value-added bioproducts. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Biorefinery; Furfural; Simulation; Sugarcane-biomass